2014
DOI: 10.1007/s00227-014-2586-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the distribution of trematode larvae in blue mussels Mytilus edulis in the North Atlantic and Arctic Oceans

Abstract: abundance of avian final hosts) on trematode infection was examined. Infection levels correlated with the interaction between local bird abundance and mussel age and density. They increased with mussel age but their dependence on mussel density and bird abundance varied among parasite genera. Prevalence and intensity increased with SSTmax for Renicola spp., but no relationship was found for Gymnophallus and Himasthla spp. The ambiguous effect of SSTmax is likely explained by the broad range of optimal temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 67 publications
2
33
0
1
Order By: Relevance
“…However, the longevity of the metacercaria and of the adult trematode are unknown. Recent studies have confirmed abundant and prevalent metacercariae infections (on average eight metacercariae per mussel; infection prevalence 83.8%) in M. edulis close to the study area (Galaktionov et al, 2015).…”
Section: Mytilus Edulis and Gymnophallus Bursicolamentioning
confidence: 90%
“…However, the longevity of the metacercaria and of the adult trematode are unknown. Recent studies have confirmed abundant and prevalent metacercariae infections (on average eight metacercariae per mussel; infection prevalence 83.8%) in M. edulis close to the study area (Galaktionov et al, 2015).…”
Section: Mytilus Edulis and Gymnophallus Bursicolamentioning
confidence: 90%
“…While such effects have been studied experimentally (e.g., Kopp and Jokela 2007;Thieltges et al 2009, Goedknegt et al 2015, surprisingly few studies have attempted to study the effects of invasive species on infection patterns in native hosts in the field (but see Paterson et al 2011Paterson et al , 2013 who used a combined approach). Parasite infection levels in native hosts are not only potentially affected by invasive species but also influenced by many other factors which have been shown to underlie the generally high spatial heterogeneities in infection levels observed in the field (Thieltges and Reise 2007;Byers et al 2008;Wilson et al 2011;Galaktionov et al 2015;Stringer and Linklater 2015). For example, the population density of native hosts often affects infection patterns across many parasite and host taxa (Arneberg 1998;Galaktionov et al 2015;Stringer and Linklater 2015;Searle et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Parasite infection levels in native hosts are not only potentially affected by invasive species but also influenced by many other factors which have been shown to underlie the generally high spatial heterogeneities in infection levels observed in the field (Thieltges and Reise 2007;Byers et al 2008;Wilson et al 2011;Galaktionov et al 2015;Stringer and Linklater 2015). For example, the population density of native hosts often affects infection patterns across many parasite and host taxa (Arneberg 1998;Galaktionov et al 2015;Stringer and Linklater 2015;Searle et al 2016). Other factors known to affect infection patterns include host size (Mouritsen et al 2003;Thieltges and Reise 2007), the supply of free-living infective stages (often approximated via preceding intermediate host densities for parasites with complex life cycles; Byers et al 2008;Wilson et al 2011;Galaktionov et al 2015) and environmental variables such as temperature, pH and salinity (Pietrock and Marcogliese 2003;Poulin 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the longevity of the metacercaria and of the adult trematode is unknown. Recent studies have confirmed abundant and prevalent metacercariae infections (on average eight metacercariae per mussel; infection prevalence 83.8%) in M. edulis close to the study area (Galaktionov et al, 2015).…”
Section: Periwinkles and Microphallids Of The Mpgmentioning
confidence: 90%